Selected issues in European tax law : the legal character of VAT and the application of general principles of justice : summary of an EFS seminar in honour of Fons Simons /: the legal character of VAT and the application of general principles of justice : summary of an EFS seminar in honour of Fons Simons. (1999) - Unknown
No abstract available